ANALISIS HUBUNGAN ANTARA KEDALAMAN TANAH DENGAN SUDUT LERENG PADA BENTUKLAHAN LERENG BAWAH VULKANIK SUB DAS KODIL PROVINSI JAWA TENGAH - , GARRI MARTHA KUSUMA WARDHANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This Study aims to 1) examine distribution of slope, 2) examine distribution of soil depth, 3) examine relationship between soil depth and slope, and 4) descriptive evaluation of landuse associated with soil depth and slope in downslope of Sumbing volcano in Kodil catchment area. This study use descriptive-qualitative method on pedeogeomorphological approach. Mapping of slope used DEM analysis and field survey. Soil depths sampling are conducted by field survey. Analysis of the relationship between soil depth and slope use crosstab. Descriptive evaluation of landuse associated with soil depth and slope use field survey methods. The results showed that the slope of the dominant classes in the study area are the slope class 1 (0â 2o) of 27.75%, slope class 3 (4 â 7o) of 23:31% and slopeclass 4 (7 â 12o) of 21:01%. The dominant soil depth classes are class 3 (2-3 m) by 45% and class 4 (> 3 m) by 42%. Slope classes shows no pattern of global morphology of slopes of the volcano. Slope class 1 to class 5 showed the slope class is inversely related to soil depth class. Slope classes 1 and 2 are in class 4 of soil depth. Slope clasess 3 and 4 are in class 3 of soil depth. Class 5 is in class 2 of soil depth. The results of this study showed a relationship between soil depth and slope in downslope of Sumbing volcano. Landuse in the research area, especially on steep slopes are still widely used for rice fields. It will cause a great threat of erosion.